Lessons from an IV drug abuser : reform the blood safety surveillance measures. - Hosseini, Mehrdad Jalalian; Bazargani, Reyhaneh; Shokri, Sadegh; Abd Latiff, Latiffah; Syed Hassan, Syed Tajuddin; Hosseinpour, Mohammad (Drunpp-Sarajevo, 2010)
An IV drug abuser donated his blood to check his HIV status for free. He concealed his past drug abuse, but appropriately chose the Confidential Unit Exclusion (CUE) option. Since the screening for transfusion transmissible infections tested negative, he tried to donate blood for a second time following a consultation session. This time, he declared his past drug behavior and was permanently rejected from further blood donation. Apart from the factors on the donor side, the health interview, donor notification, and post-CUE consultation procedures should also be sufficient for making such donors feel safe about stating their past history of risky behaviors.